2019
DOI: 10.1111/afe.12328
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Zeugodacus tau species complex in Thailand

Abstract: 1 The tephritid fruit fly Zeugodacus tau is a serious agriculture pest, especially of cucurbits in Thailand, where it is classified as a complex species of nine siblings (Z. tau A, B, C, D, E, F, G, I and J). 2 Based on single-strand conformation polymorphism (SSCP) analysis, 33 distinct mitochondrial cytochrome c oxidase subunit I (mtCOI) haplotypes were found in three sibling species, Z. tau A, C and J, in Thailand. Genetic structure analysis of the population revealed relatively large genetic differences am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…We collected samples of Z. tau adults (n = 3-5) from the study area to confirm their identity. These individuals were tested in the laboratory using their mtCOI sequences (Kitthawee and Julsirikul, 2019). The results of the identification revealed that the Z. tau individuals belonged to Z. tau A.…”
Section: Rearing and Temperature Settingsmentioning
confidence: 99%
“…We collected samples of Z. tau adults (n = 3-5) from the study area to confirm their identity. These individuals were tested in the laboratory using their mtCOI sequences (Kitthawee and Julsirikul, 2019). The results of the identification revealed that the Z. tau individuals belonged to Z. tau A.…”
Section: Rearing and Temperature Settingsmentioning
confidence: 99%
“…This may be evidence for repeated, human-assisted movement of fruit flies to that region. Human carriage of fruit fly infested fruit with resultant panmixia has been used as an explanation for the lack of genetic structuring in numerous pest fruit fly species [38,[52][53][54]. While often proposed, this explanation must assume for B. jarvisi and B. tryoni, that human movement of infested fruit is sufficiently extensive to account for the lack of genetic differentiation across >2000km and to hide the historical genetic signatures of multiple, well documented biogeographic barriers.…”
Section: Role Of Human Mediated Dispersal In B Jarvisi Population Str...mentioning
confidence: 99%
“…Human carriage of fruit fly infested fruit with resultant panmixia has been used as an explanation for the lack of genetic structuring in numerous pest fruit fly species (38,(51)(52)(53). While often proposed, this explanation must assume for B. jarvisi and B. tryoni, that human movement of infested fruit is sufficiently extensive to account for the lack of genetic differentiation across >2000km and to hide the historical genetic signatures of multiple, well documented biogeographic barriers.…”
Section: Role Of Human Mediated Dispersal In B Jarvisi Population Str...mentioning
confidence: 99%